2020
DOI: 10.3390/en13030763
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Saccharification of Laminaria japonica by Cellulase for the Production of Reducing Sugars

Abstract: Enzymatic saccharification of Laminaria japonica seaweed biomass was optimized by four independent factors (enzyme dose, hydrolysis time, pH, and temperature) using response surface methodology (RSM). To confirm the significance of the quadratic model, an analysis of variance (ANOVA) was performed, and the F-value of 8.76 showed that the regression model was highly significant (≤0.1%). In the accuracy study, average recoveries were in the range of 97.00% to 98.32%. The optimum experimental conditions were an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Utilizing information obtained from previous enzymatic hydrolysis [28], Celluclast ® 1.5 L (8.17% v/w biomass ), a hydrolysis time of 26.4 h, a pH of 4.1, and a temperature of 42.6 • C were selected as the predicted conditions. Enzymatic hydrolysis was conducted after the hydrothermal acid pretreatment under the predicted conditions using RSM.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing information obtained from previous enzymatic hydrolysis [28], Celluclast ® 1.5 L (8.17% v/w biomass ), a hydrolysis time of 26.4 h, a pH of 4.1, and a temperature of 42.6 • C were selected as the predicted conditions. Enzymatic hydrolysis was conducted after the hydrothermal acid pretreatment under the predicted conditions using RSM.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%
“…Previous studies have reported combined treatment (sequential hydrolysis) to increase the reducing sugar yield [28]. Therefore, this study was aimed to perform sequential hydrolysis using hydrothermal acid pretreatment followed by enzymatic hydrolysis to determine the RS y .…”
Section: Introductionmentioning
confidence: 99%